Semaphorin SEMA3F and VEGF Have Opposing Effects on Cell Attachment and Spreading - Patrick Nasarre; Bruno Constantin; Lydie Rouhaud; Thomas Harnois; Guy Raymond; Harry A. Drabkin; Nicolas Bourmeyster; Joëlle Roche (Neoplasia: An International Journal for Oncology Research, 2003)
SEMA3F, isolated from a 3p21.3 deletion, has antitumor activity in transfected cells, and protein expression correlates with tumor stage and histology. In primary tumors, SEMA3F and VEGF surface staining is inversely correlated. Coupled with SEMA3F at the leading edge of motile cells, we previously suggested that both proteins competitively regulate cell motility and adhesion. We have investigated this using the breast cancer cell line, MCF7. SEMA3F inhibited cell attachment and spreading as evidenced by loss of lamellipodia extensions, membrane ruffling, and cell-cell contacts, with cells eventually rounding-up and detaching. In contrast, VEGF had opposite effects. Although SEMA3F binds NRP2 with 10-fold greater affinity than NRP1, the effects in MCF7 were mediated by NRP1. This was determined by receptor expression and blocking of anti-NRP1 antibodies. Similar effects, but through NRP2, were observed in the C100 breast cancer cell line. Although we were unable to demonstrate changes in total GTPbound Rac1 or RhoA, we did observe changes in the localization of Rac1-GFP using time lapse microscopy. Following SEMA3F, Rac1 moved to the base of lamellipodia and — with their collapse — to the membrane. These results support the concept that SEMA3F and VEGF have antagonistic actions affecting motility in primary tumor cell.